Enhanced design consideration for mobility support in internet of things / Wan Fariza Wan Abdul Rahman and Aisha Hassan Abdalla Hashim - Abdul Rahman, Wan Fariza Wan; Abdalla Hashim, Aisha Hassan (2022)
Mobility assistance is necessary for many Internet of Things applications (IoT), including real-time patient monitoring and vehicle tracking systems. Sadly, the proposed standard Routing Protocol for Low-Power and Lossy Networks (RPL) only takes into account static wireless sensor networks (WSN). For RPL, solid mobility support is essential to ensuring ongoing device connectivity. Additionally, inadequate mobility support causes data loss, increased energy consumption, longer delays, and a decline in application performance. Numerous solutions have been put up to address the mobility challenges, but none of them take into account various mobility models about pertinent elements. This article offers a variety of mobility models for use in mobile IoT applications. Understanding the mechanisms of various mobility models enables more effective implementation of application-specific RPL mobility assistance. Mobility patterns, or the actual movement behaviour of moving objects, are closely related to mobility models. Velocity, obstructions, whether a movement is solo or group-based, and other elements affect how a movement behaves. This work proposes the improved design of mobility support for RPL while taking into account all the variables and various mobility models.